Utilization of Blockchain for Marine Products Tracking - Stephane, Ilfa; Saputra, Heru; Alhaj, Nasrudin; Putra, Lakry Maltaf (The Indonesian Journal of Computer Science, 2022)
Many marine product companies currently have not implemented blockchain potentials in tracking systems. There could be found many errors in the transactions record. The purpose of this research is to implement blockchain as a fraud prevention system for transactions in marine product companies. This research is qualitative-exploratory research with data collection using documentation techniques from related literature. This study concludes that Blockchain can be used as an alternative to fraud prevention. Blockchain can be used because there is transparency with a distributed system, which makes the whistleblowing system more effective and independent, in fully implementing the principles of GCG (Good Corporate Governance). The results of the advanced system designed at a marine product company are to facilitate data collection of all goods to be sent this providing high-security guarantees because it implements a blockchain security system in this system, and places an integrated tracking system so that data and goods sent during the transaction can be tracked.